Enhancing osteogenesis and angiogenesis functions for Ti-24Nb-4Zr-8Sn scaffolds with methacrylated gelatin and deferoxamine - Xu, Qian; Bai, Yun; Li, Shujun; Hou, Wentao; Hao, Yulin; Yang, Rui; Li, Xiaowu; Zhang, Xing (Frontiers in Bioengineering and Biotechnology, 2024)
Repair of large bone defects remains challenge for orthopedic clinical treatment.Porous titanium alloys have been widely fabricated by the additive manufacturing, which possess the elastic modulus close to that of human cortical bone, good osteoconductivity and osteointegration. However, insufficient bone regeneration and vascularization inside the porous titanium scaffolds severely limit their capability for repair of large-size bone defects. Therefore, it is crucially important to improve the osteogenic function and vascularization of the titanium scaffolds. Herein, methacrylated gelatin (GelMA) were incorporated with the porous Ti-24Nb-4Zr-8Sn (Ti2448) scaffolds prepared by the electron beam melting (EBM) method (Ti2448-GelMA). Besides, the deferoxamine (DFO) as an angiogenic agent was doped into the Ti2448-GelMA scaffold (Ti2448-GelMA/DFO), in order to promote vascularization.The results indicate that GelMA can fully infiltrate into the pores of Ti2448 scaffolds with porous cross-linked network (average pore size: 120.2 ± 25.1 μm). Ti2448-GelMA scaffolds facilitated the differentiation of MC3T3-E1 cells by promoting the ALP expression and mineralization, with the amount of calcium contents ~2.5 times at day 14, compared with the Ti2448 scaffolds. Impressively, the number of vascular meshes for the Ti2448-GelMA/DFO group (~7.2/mm 2 ) was significantly higher than the control group (~5.3/mm 2 ) after cultivation for 9 hours, demonstrating the excellent angiogenesis ability. The Ti2448-GelMA/DFO scaffolds also exhibited sustained release of DFO, with a cumulative release of 82.3% after 28 days. Therefore, Ti2448-GelMA/DFO scaffolds likely provide a new strategy to improve the osteogenesis and angiogenesis for repair of large bone defects.